Approaches to the territory-museum management model based on practical cases - Bringas, Andrea Caridad (2020)
The recent concept of Territory-museum arose in the second half of the 90s, as a strategy to define a management model based on the musealization of a territory, in order to contribute to the sustainable development of rural areas. In that model, the following are emphasized: interventions in the conservation of natural and cultural heritage, tangible and intangible; the active and leading participation of society; and, the implementation of a territorial interpretation plan. In the present work, the origins of the concepts of ecomuseums and theories of interpretation will be detailed, and the characteristics of the Territory-museum and the elements that are part of it, will be explained. Finally, there will be a comparative analysis of three cases in Italy, Spain and Argentina, in order to show the shared characteristics and differences, within the framework of the scope and regional variability of this innovative concept. All of this, will let to present a brief discussion and conclusions.